Voices of Student-Teachers on Teacher Education During Covid-19 Pandemic: A Case Study of D.El.Ed Students - Khalil, Sumbul; Gupta, Urvashi (Voices of Teachers and Teacher Educators, 2022)
The Government of India declared a countrywide lockdown of all educational institutions on 16th March, 2020, due to the spread of Pandemic COVID-19. A year has passed since then when the entire educational system in India, including school and higher education institutes switched from face to face mode of teaching learning to virtual mode. The educational institutions chose to operate partially or completely through online mode acting according to the circumstances and ease of lifting of the lockdown. In the present study, student teachers of D.El.Ed participated to share their experiences and reflections related to classroom teaching- learning (online and traditional), assignments and assessment, workshops, School Experience Programme (SEP) and overall learning in a teacher education course during COVID-19 pandemic.